2003
DOI: 10.1080/110241598750004904
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal stab wounds: the role of selective management

Abstract: We managed to minimise the number of negative and unnecessary laparotomies. We emphasise that the selective approach may easily be applied in teaching hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 11 publications
0
24
0
6
Order By: Relevance
“…[18] Bu bilgiler ışığında özellikle DKAY'si olan hastalarda SNOY yaklaşımı son dönemlerde yaygın olarak uygulanmaktadır. [4,7,8,10] Son yirmi yılda görüntüleme teknolojisindeki gelişmelere ve daha kolay erişilebilirliğe bağlı olarak SNOY ateşli silaha bağlı karın yaralanmalarında da güvenli ve etkili bir şekilde kullanılmaya başlamıştır. [11][12][13][14][15][16] Ancak bununla ilgili veriler kısıtlıdır ve sadece Amerika ve Güney Afrika'daki birkaç merkezden bildirilmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[18] Bu bilgiler ışığında özellikle DKAY'si olan hastalarda SNOY yaklaşımı son dönemlerde yaygın olarak uygulanmaktadır. [4,7,8,10] Son yirmi yılda görüntüleme teknolojisindeki gelişmelere ve daha kolay erişilebilirliğe bağlı olarak SNOY ateşli silaha bağlı karın yaralanmalarında da güvenli ve etkili bir şekilde kullanılmaya başlamıştır. [11][12][13][14][15][16] Ancak bununla ilgili veriler kısıtlıdır ve sadece Amerika ve Güney Afrika'daki birkaç merkezden bildirilmiştir.…”
Section: Discussionunclassified
“…[1] Penetran karın travmalı hastaların yönetiminde temel hedefler; mortalite ve morbiditiyi en aza indirmek, negatif veya non-terapötik laparotomiden kaçınmak ve maliyeti azaltmaktır. [2][3][4] Bu amaçlar doğrultusunda birçok travma merkezinde acil laparotomi endikasyonu olmayan delici-kesici alete bağlı karın yaralanmalarında (DKAY) 'selektif non-operatif yöne-tim' (SNOY) genel kabul gören yaklaşım haline gelmiştir. [5][6][7][8][9][10] Son yirmi yılda özellikle gelişmiş görüntüleme teknikleri sayesinde SNOY yaklaşımının ateşli silaha bağlı karın yaralanmalarında da (ASY) etkili ve güvenilir olduğu gösterilmiştir.…”
Section: Introductionunclassified
“…Studies have shown that most commonly affected hollow and solid organs after penetrating abdominal trauma are small intestines (30%) and liver (19%), respectively. [20][21][22] Colon (18%), stomach (13%), pancreas, and duodenum follow. [21,22] Bowel rupture following penetrating abdominal trauma lead to the gas and other intestinal ingredients leak into the peritoneum resulting in peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Colon (18%), stomach (13%), pancreas, and duodenum follow. [21,22] Bowel rupture following penetrating abdominal trauma lead to the gas and other intestinal ingredients leak into the peritoneum resulting in peritonitis. [23] Small bowel injury is rarely diagnosed preoperatively, especially when there are no specific signs of haemoperitoneum or peritonitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation